Photographic assessment of facial components in facial esthetics as perceived by orthodontists, artists, and photographers - An In vivo study - Khaniya Bharathan; Indra Annamalai; Prema Anbarasu; Saravana Kumar Subramanian (Wolters Kluwer Medknow Publications, 2022)
Background: Facial esthetics was primarily the subject of study for artists and philosophers. Facial appearance is an essential diagnostic criterion for a complete comprehensive orthodontic treatment planning. The aim of this study was to establish the perception of facial esthetics by different professionals, namely orthodontists, artists, and photographers, and to investigate the most influential facial characteristics involved in rating the overall attractiveness. Materials and Methods: Twenty-two subjects of age 18-24 years fulfilling the inclusion criteria were selected as the study samples. The subjects were asked to relax, gently touch the lips together, and then start smiling. This dynamic range of smile was video recorded using a digital camera. This video was then converted into 300 frames. The frame that best represented the subjects' natural/posed unstrained social smile was selected and cropped to create three types of images: the face with the smile, the face without the smile, and the smile image. The evaluators (orthodontists, artists, and photographers) were instructed to answer the questions from 1 to 8 looking at image 1 (face with smile), question 9 by looking at image 2 (face without the smile), and questions 10 and 11 by looking at image 3 (smile only). Results: According to orthodontists and artists, the feature most strongly associated with overall attractiveness was symmetry of face, whereas the photographers showed the highest score for cheekbones. The highest correlation was found between the orthodontist and artist groups. Conclusion: The perception by the three professionals confirms that the overall facial attractiveness is more important than dental attractiveness.